Topinambur (Helianthus tuberosus) and yacon (Smallanthus sonchifolius): nutraceutical crops? - Di Barbaro, Maria Gabriela (2022)
This review is about two crops, topinambur (Helianthus tuberosus L.) and yacón [Smallanthus sonchifolius (Poeppig & Endlicher) H. Robinson], which due to their properties should be considered as nutraceutical foods. The common characteristics they present are discussed, such as belonging to the same botanical family (Asteraceae), being ancestral crops produced for their different uses (horticultural, forage and industrial), and for generating tubers that store carbohydrates such as inulin and fructooligosaccharides (FOS). In addition, these compounds are considered to have beneficial effects on nutrition and human health, which would allow them to be defined as nutraceutical foods. Therefore, the objective of this review is to contribute to the dissemination of knowledge about the characteristics of topinambur (Helianthus tuberosus) and yacón (Smallanthus sonchifolius) crops, in order to improve their production, consumption and use.